Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acs.bioconjchem.7b00043
|View full text |Cite
|
Sign up to set email alerts
|

Specific Ligation of Two Multimeric Enzymes with Native Peptides and Immobilization with Controlled Molar Ratio

Abstract: d-Amino acid oxidases (DAAOs) are flavor enzymes and have been used in resolution of racemic amino acids and manufacturing of pharmaceuticals. However, the evolved HO during the catalysis has deleterious and inhibitory effects. Decomposition of the hydrogen peroxide by catalase (CAT) can eliminate the negative effects. DAAO and CAT are dimeric and tetrameric proteins, respectively. Here, the N-terminus of the DAAO subunits has been specifically ligated to the C-terminus of the CAT subunits with native peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
(77 reference statements)
0
18
0
Order By: Relevance
“…The apparent K m value of 12.02 mM f-LaMOF@DAAO is smaller than the K m value of 15.37 mM free DAAO. 41 It is indicated that f-LaMOF@DAAO exhibited an enhanced affinity toward the substrate. The catalysis efficiency can be measured by the k cat / K m ratio.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The apparent K m value of 12.02 mM f-LaMOF@DAAO is smaller than the K m value of 15.37 mM free DAAO. 41 It is indicated that f-LaMOF@DAAO exhibited an enhanced affinity toward the substrate. The catalysis efficiency can be measured by the k cat / K m ratio.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The expression of enzymes is briefly described as follows [34]. E. coli BL21 harboring the plasmids were grown at 25 • C in Luria-Bertani (LB) medium with 50 µg/mL Amp.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Previously, we have specifically ligated two multimeric enzymes with native peptides through intein-mediated in vivo subunit splicing (Du et al, 2017;Li et al, 2018). Herein, we develop the methodology, by using the coiled-coil association of an arginine-rich leucine zipper motif (Z R ) (Moll et al, 2001) and a glutamic acid-rich leucine zipper motif (Z E ) (Moll et al, 2001) to trigger the intein-mediated in vivo subunit splicing.…”
Section: Introductionmentioning
confidence: 99%